Serum- and Glucocorticoid-Inducible Kinase-1 (SGK-1) Plays a Role in Membrane Trafficking in Caenorhabditis elegans - Zhu, Ming (Public Library of Science, 2015)

(untitled) (PLoS One)
The mammalian serum- and glucocorticoid-inducible kinase SGK1 regulates the endocytosis of ion channels. Here we report that in C. elegans sgk-1 null mutants, GFP-tagged MIG-14/Wntless, the sorting receptor of Wnt, failed to localize to the basolateral membrane of intestinal cells; instead, it was mis-sorted to lysosomes. This effect can be explained in part by altered sphingolipid levels, because reducing glucosylceramide biosynthesis restored the localization of MIG-14::GFP. Membrane traffic was not perturbed in general, as no obvious morphological defects were detected for early endosomes, the Golgi apparatus, and the endoplasmic reticulum (ER) in sgk-1 null animals. The recycling of MIG-14/Wntless through the Golgi might be partially responsible for the observed phenotype because the subcellular distribution of two plasma membrane cargoes that do not recycle through the trans-Golgi network (TGN) was affected to a lesser degree. Consistently, knockdown of the ArfGEF gbf-1 altered the distribution of SGK-1 at the basolateral membrane of intestinal cells. In addition, we found that sgk-1(RNAi) induced unfolded protein response in the ER, suggesting at least an indirect role of SGK-1 early in the secretory pathway. We propose that SGK-1 function is required for lipid homeostasis and that it acts at different intracellular trafficking steps.